1997
DOI: 10.1164/ajrccm.155.1.9001315
|View full text |Cite
|
Sign up to set email alerts
|

Time course of hypoxic pulmonary vasoconstriction: a rabbit model of regional hypoxia.

Abstract: There is disagreement in the literature about the time required for hypoxic constriction of pulmonary vessels to reach its full intensity. Some studies suggest that only minutes are required, others that several hours are needed. We examined the time course over 6 h of changes in pulmonary shunt (as a fraction of cardiac output) following induction of unilateral hypoxia by collapse or liquid filling of the left lung in 47 anesthetized rabbits. The time course was examined at four degrees of lung inflation: dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Different, overlapping mechanisms might be responsible for the initial rapid increase and subsequent slow intensification of pulmonary artery pressures (Vejlstrup et al . ) in response to hypoxia, and delaying our measurements to 90–120 min might have yielded different results. However, at altitude, where subjects were hypoxic for 8–12 days, RIPC failed to elicit any changes in PASP, indicating that the time of measurement probably does not explain our lack of effect at SL.…”
Section: Discussionmentioning
confidence: 99%
“…Different, overlapping mechanisms might be responsible for the initial rapid increase and subsequent slow intensification of pulmonary artery pressures (Vejlstrup et al . ) in response to hypoxia, and delaying our measurements to 90–120 min might have yielded different results. However, at altitude, where subjects were hypoxic for 8–12 days, RIPC failed to elicit any changes in PASP, indicating that the time of measurement probably does not explain our lack of effect at SL.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been found (4,21,22,32) in isolated lungs and in intact and open-chest animals that sustained alveolar hypoxia provokes a prolonged PAP elevation, but the underlying mechanisms have rarely been addressed. Our group (27) previously showed that a biphasic pressor response is regularly elicited by prolonged hypoxia in perfused rabbit lungs, and this was also noted in intact rabbits (21,22), in vivo perfused lungs of the dog, and intact dogs (4, 31) as well as in isolated ferret lungs (32). A new observation of the present study is the fact that 120-180 min of sustained (uninterrupted) alveolar hypoxia sufficed to cause a persistent elevation in posthypoxic "baseline" PAP.…”
Section: General Features Of Sustained Alveolar Hypoxiamentioning
confidence: 99%
“…For both the acute and sustained phase of HPV there is ongoing discussion whether mitochondria, NADPH oxidases, or alternative systems are the underlying oxygen sensors and whether they are regulated by identical or by different mechanisms (2,(6)(7)(8)(9). Biphasic hypoxic vasoconstrictor responses have repeatedly been shown to occur in isolated vessels, but few studies have focused on the regulation in the intact organ (9)(10)(11)(12)(13).…”
mentioning
confidence: 99%